Verba Mental Kognisi Pada Novel “Hujan” Karya Tere Liye - Siti Nabilah; Sri Utami; Dedy Setyawan (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the cognitive mental verbs found in the novel Hujan by Tere Liye. Cognitive mental verbs are part of mental processes related to thinking, understanding, remembering, and evaluating, which are used to express the characters’ inner states and enrich the story’s meaning. The approach used in this study is a qualitative approach with a descriptive method. The data source in this study is the novel Hujan by Tere Liye, while the research data consists of sentences containing cognitive mental verbs. The data obtained were analyzed to identify the forms and functions of cognitive mental verbs in depicting the characters’ thought processes. The results of the study indicate that the cognitive mental verbs identified include verbs such as thinking, remembering, realizing, understanding, guessing, and recalling. These verbs are used to depict the characters’ cognitive activities in understanding situations, processing experiences, and developing the plot in greater depth.